PENGEMBANGAN PANTAI SEBAGAI WISATA BAHARI DI DESA DADAP KECAMATAN SAMBELIA KABUPATEN LOMBOK TIMUR - Misbahuddin, Misbahuddin; Romara, Adam; S, Fatma Faradilla; Lestari, Ewang; R, Tri Wulandari; Ghiffary, Nabil Al; P, Nurul Fitriani; A., Sirrul Aini S.; Ilham, Nazriel; Supriatin, Lili; Muflin, M. (Jurnal Wicara, 2023)
Real Work Lecture (KKN) is a form of community service carried out by universities. In the KKN activities carried out in Dadap Village, Sambelia District, East Lombok Regency. University of Mataram KKN-T students carry out activities with the aim of structuring village potential development and economic empowerment of the Dadap Village community. The purpose of implementing this KKN is to answer various social issues that are found, among others, in carrying out village development matters. The result of this activity is building tourism potential in Dadap Village, Sambelia District, East Lombok Regency.